ANALISIS USABILITY PADA APLIKASI SISTEM PELAYANAN RAKYAT SID`OARJO (SIPRAJA) MENGGUNAKAN METODE HEURISTIC EVALUATION DAN SYSTEM USABILITY SCALE - firzatullah, arsa (Jurnal Manajemen dan Teknologi Informasi, 2024)
This study aims to analyze the usability of the Sidoarjo Public Service System (SIPRAJA) application using Heuristic Evaluation and the System Usability Scale (SUS) methods. The SUS results provide an average score of 49.63. The Heuristic Evaluation identifies problems and strengths based on design principles, while SUS quantitatively assesses the application's usability. The Heuristic Evaluation results show that most usability aspects fall into the "poorly functioning features" category, with some aspects such as "Error Prevention" receiving better ratings. indicating that the SIPRAJA application requires significant improvements to enhance usability and user satisfaction. This research provides a basis for improvement recommendations to increase the efficiency and effectiveness of public services through this application.